Pengembangan Kapasitas Kewirausahaan Digital bagi Badan Santunan Yatim di Depok - Ida Zuniarti; Instianti Elyana; Sri Rusiyati (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Limited digital literacy and technology-based marketing capacity pose challenges to entrepreneurship development at the Badan Santunan Yatim in Depok. The limited use of social media as a promotional tool has prevented the community from optimally developing its economic potential. This community service program aims to enhance digital entrepreneurship capacity through training on the use of social media as a marketing platform. The method employed a participatory approach, including interactive training sessions, hands-on practice in creating promotional content, mentoring in managing business accounts, and evaluation through pretests and posttests. The results indicate an improvement in participants’ understanding and skills in utilizing social media for business promotion. This is reflected in the increased evaluation scores and the participants’ ability to independently produce digital content, reaching 94.87%. The program contributes to strengthening economic self-reliance and supporting the sustainability of digital-based businesses within the target community.